ANALYSIS OF COMBUSTIBLE FRACTIONS IN MIXED MUNICIPAL WASTE AND PACKAGING AND CALCULATION OF ENERGY VALUE - Buble, Ivana; Jerina, Simon; Seme, Sebastijan; Stergar, Janja (Journal of Energy Technology, 2024)
The present article analyses combustible fractions in mixed municipal waste and packaging and the calculation of energy value. Methods of thermal treatment of waste and methods of preparation of alternative fuels and classifications are presented and described. The article describes the method of analysis of caloric values with which we determined the energy values of individual fractions. For the research, we also used two thermal analyses, with which we considered individual fractions, thermogravimetric analysis, and differential dynamic calorimetry. The article presents the results of both thermal analyses, with which we observe the responses of individual types of plastics at different temperatures and the change in physical and chemical properties. The problem we have analysed in this article is mainly recyclable plastic that can no longer be reused due to various factors. The results of the structural analysis of household waste collection are also presented and described; on the basis of the analysis, the energy value of the container of mixed municipal waste and the reasonableness of waste reuse are recalculated.